Assessment of the Combined Efficacy of Needling and the Use of Silicone Gel in the Treatment of C-Section and Other Surgical Hypertrophic Scars and Keloids. (September 2016) - Fabbrocini, Gabriella; Marasca, Claudio; Ammad, Sadia; Brazzini, Benedetta; Izzo, Rosanna; Donnarumma, Marianna; Monfrecola, Giuseppe
ABSTRACT: OBJECTIVE: To evaluate the individual effectiveness of needling therapy using the Dermapen (Dermapen, Salt Lake City, Utah) and topical therapy with silicone gel (Kelo-cote, Sinclair Pharma, London, England), and their combined effectiveness for the treatment of linear surgical scars, hypertrophic scars, and keloids. MATERIALS AND METHODS: Twenty patients were randomly selected and equally divided into 2 groups (A and B), with each group of 10 including 6 patients with keloids and 4 with hypertrophic scars. Treatment assignments were random. In group A, the entire scar was treated by skin needling, with silicone gel applied to half of the scar. Patients in group B were treated with silicone gel on the whole scar, with only half of the scar also treated with skin needling. During follow-up visits, clinical photographs, evaluation of the scars' thickness, skin ultrasound, and modified Vancouver Scar Scale were performed. RESULTS: Group A showed an average improvement of 68% ( P < .01) on the half of the scar with the combination treatment (skin needling plus silicone gel) compared with a 52% improvement on the half of the scar that was treated with only skin needling. Group B showed an average improvement of 63% ( P < .01) where the combination treatment was performed, compared with 47% improvement on the area treated with only the silicone gel. CONCLUSIONS: In conclusion, the combination of these 2 treatments is safe and effective for the treatment of hypertrophic scars and keloids. These modalities achieved favorable results with each patient adhering to the study paramenters.